AB0830-HPR Feelings of competence and relatedness during physical activity are related to well-being in rheumatoid arthritis patients: preliminary findings from a randomized control trial. (23rd January 2014) - Rouse, P. C.; Duda, J. L.; Veldhuijzen Van Zanten, J. J.; Metsios, G. S.; Ntoumanis, N.; Yu, C.-A.; Kitas, G. D.
Abstract : Background: Rheumatoid arthritis (RA) is a chronic inflammatory disease that causes joint pain, swelling and stiffness with eventual structural damage leading to physical dysfunction. Consequently, people with RA tend to experience fatigue and psychological distress. As proposed by Self-determination Theory (SDT), feelings of ownership, competence and relatedness (basic human psychological needs) during physical activity (PA) are predicted to alleviate such disease-related symptoms and improve psychological well-being in RA patients. Objectives: To examine whether a Self-determination Theory-based intervention fosters basic need satisfaction. In addition, to examine the relationships between need satisfaction and indicators of psychological well-being and disease related symptoms (i.e., fatigue, depression and subjective vitality) in patients with RA following a 3 month exercise programme. Methods: A RCT compared two 3 month exercise programmes. The control arm participants received a standard exercise referral programme. Patients in the experimental arm received an additional psychological intervention that aimed to foster basic need satisfaction through contacts with a SDT trained PA advisor. Participants completed the following validated measures at the end of the 3 month exercise programme; Psychological Need Satisfaction in Exercise Scale, Multidimensional Assessment of Fatigue Scale, Hospital Anxiety and Depressions Scales, and Subjective Vitality Scale. Results: Preliminary analyses ( N = 41 patients; M age = 55.4 yrs) indicated that the intervention arm patients ( N = 22) reported significantly greater competence need satisfaction [ F (1, 39) = 6.9, p = .01] than the control arm. Differences between arms for autonomy [ F (1, 39) = 3.63, p = .06] and relatedness [ F (1, 39) = .88, p = .36] favoured the intervention. Pearson correlation coefficients from all data revealed feelings of competence and relatedness after the exercise programme were significantly and negatively related to depressive symptoms ( r = -.43, p = .006 and r = -.39, p = .02 respectively). Competence also demonstrated a significant positive relationship with subjective vitality ( r = .42, p = .01) and a negative relationship with fatigue ( r = -.49, p = .002) at the end of the 3 month exercise programme. Conclusions: Results suggest that a SDT-grounded PA intervention promotes need satisfaction during exercise. In addition, need satisfaction is associated with reductions in fatigue and enhancements in psychological well-being in patients with RA. Subsequent work will examine follow-up effects at 6 and 12 months. Disclosure of Interest: None Declared